2006
DOI: 10.1158/0008-5472.can-05-4533
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Regulates Cell Sensitivity to Cisplatin-Induced Apoptosis through S-Nitrosylation and Inhibition of Bcl-2 Ubiquitination

Abstract: Cisplatin is a potent cytotoxic agent commonly used for the treatment of solid tumors. However, tumor cell-acquired resistance to cisplatin-induced apoptosis is a major limitation for efficient therapy, as frequently observed in human lung cancer. Nitric oxide (NO) is a key regulator of apoptosis, but its role in cisplatin-induced cell death and the underlying mechanism are largely unknown. Previous studies indicate increased NO synthase activity and elevated NO production in lung carcinomas, which correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 45 publications
6
100
0
1
Order By: Relevance
“…The protocol we used was designed to expose DCs to NO selectively and only ex vivo to minimize the systemic effects of NO in vivo. These effects of NO in the case of tumors are complex, resulting from a combination of cytotoxic and cytostatic actions on tumor cells, and protumorigenic functions, including stimulation of angiogenesis and down-regulation of immune responses (13,14); in addition, systemic NO may change sensitivity to anticancer drugs in vivo (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol we used was designed to expose DCs to NO selectively and only ex vivo to minimize the systemic effects of NO in vivo. These effects of NO in the case of tumors are complex, resulting from a combination of cytotoxic and cytostatic actions on tumor cells, and protumorigenic functions, including stimulation of angiogenesis and down-regulation of immune responses (13,14); in addition, systemic NO may change sensitivity to anticancer drugs in vivo (18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated NO levels have been associated with cancer cell behaviors such as anoikis resistance, increased cell motility, and chemoresistance (8,60,67). To test whether NO might affect epithelial-mesenchymal transition (EMT) properties of lung cancer cells, we first determined the appropriate noncytotoxic concentrations of NO donor used in this study.…”
Section: Effect Of Dpta Nonoate On Human Lung Cancer Cell Epithelial-mentioning
confidence: 99%
“…Not only is NOS expression detectable in various cancers, but also the NO level is frequently upregulated in tumor areas (26,36). Previous studies indicated that NO could render cells resistant to death induced by various stimuli (7,8,67). NO also regulates cancer cell migration and invasion (60), and increased NOS expression and activity have been reported in metastatic lung cancer cells (57).…”
mentioning
confidence: 99%
“…Amplification and overexpression of BCL2 occurs in many malignancies, including small cell lung carcinoma, and impairs intrinsic apoptotic signaling (16). Moreover, the overexpression of BCL2 has been showed to inhibit cisplatininduced cell death in non-small cell lung cancer H460 cells (17). The findings of the current study indicate that, by targeting MCL1 and BCL2 proteins, cycloartobiloxanthone may have utility in the treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 58%